(untitled) (Web of Teachers: Inderscience Research, 2024)
The article is devoted to one of the most acute problems of teaching Russian as a foreign language - interference. It reveals the features of taking into account interlingual transfer and interference in the organization of the process of teaching Russian as a foreign language. Evidence is given that the use of the native language of students in the process of teaching Russian as a foreign language is considered methodologically sound and expedient, and also makes it possible to increase the efficiency of the educational process.